Exploring the Determinants of Job Hopping Among Generation Z - Marlenaa, Marlenaa; Ariani, Lita; Marsha, Gladis Corinna (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study aims to determine whether psychological capital and work-life balance influence job hopping among Generation Z employees in Banjarmasin City. This study uses a quantitative correlational approach. The research respondents numbered 155 people using a purposive sampling method. The questionnaire was distributed through social media, such as WhatsApp and Instagram. The research data were analyzed using multiple linear regression. The results of the F-test analysis showed that psychological capital and work-life balance simultaneously influence job hopping among Generation Z employees in Banjarmasin City (F = 161.945 and p = 0.001). At the same time, the t-test results showed that psychological capital positively influences job hopping, which contradicts the hypothesis proposed by the researcher (t = 14.684 p = 0.001). However, the results of the analysis t-test on work-life balance showed an adverse effect on job hopping (t = -2.289 and p = 0.023), which aligns with the hypothesis proposed by the researcher. The conclusion is that although psychological capital and work-life balance simultaneously influence job hopping among Generation Z employees in Banjarmasin City, the influence of psychological capital on job hopping is positive. In contrast, the influence of work-life balance on job hopping is negative. The results of this study are expected to add information and knowledge references in the industrial and organizational psychology sector, especially for organizations managing Generation Z employees.